Obstetric Correlates of Birth Preparedness and Complication Readiness Among Pregnant Women Attending Antenatal Clinics in South-East Senatorial District, Rivers State - Mandah, Florence Uchechi; Peter-Kio, Opirite Boma (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
This study investigated the obstetric correlates of birth preparedness and complication readiness among pregnant women in the South-East Senatorial District, Rivers State. A descriptive correlational research design was adopted with a population consisting of 1,965 women attending antenatal clinic in the South East senatorial district of Rivers State. The sample size was 983, which was selected using a multi-stage sampling procedure. Data was collected using a structured questionnaire with a reliability coefficient of 0.81. Data collected were analysed with the aid of the Statistical Product for Service Solution (SPSS V-23) using the Pearson Correlation at a 0.05 level of significance. The finding of this study revealed that there was a significant relationship between birth preparedness and complication readiness and obstetric variables such as previous mode of delivery (n = 969; r = 0.59; p<0.05); previous history of hemorrhage (n = 969; r = 0.47; p<0.05); availability of skilled birth attendants (n = 969; r = 0.28; p<0.05); and antenatal care services utilization (n = 969; r = 0.67; p<0.05). These findings underscore the importance of previous delivery experiences, history of obstetric complications, access to skilled birth attendants, and antenatal care utilisation in ensuring maternal and neonatal well-being. The study concluded that adequate birth preparedness and complication readiness among pregnant women in the South-East Senatorial District, Rivers State, requires a holistic approach that combines spousal involvement and knowledge of obstetric emergencies. It was recommended that healthcare workers particularly nurses, midwives and obstetricians should direct their focus to public health interventions to improve antenatal education, enhance access to skilled birth attendants, and address barriers to quality maternal healthcare services as this will contribute to better birth preparedness, reduce complications and improve the overall maternal and neonatal health outcomes.